SHARIA FINTECH: PIONEERING THE EVOLUTION OF ISLAMIC FINANCIAL SYSTEMS IN INDONESIA - Muslina, Muslina; Hayati, Husna; Rofizar, Heny (J-ISCAN: Journal of Islamic Accounting Research, 2024)
Indonesia is confronted with major challenges in its efforts to foster collaboration with fintech in order to navigate the free market era. The continuity of a sharia financial institution's business is at risk if it fails to adapt to the flow of information and technology, which will make it challenging to compete in a free market. A literature study is conducted by analyzing a variety of secondary data from OJK publications, Fintech websites, AFSI websites, and supporting articles on the results of the study. The data was subsequently analyzed using a descriptive qualitative approach to actualize an array of viewpoints regarding the role of fintech in the development of the sharia financial institution system. The results of this study's search indicate that sharia financial institutions have enrolled in the Indonesian Sharia Fintech Association (AFSI). However, some institutions continue to employ conventional methods in their operations, such as microfinance institutions, which have significant potential but have not yet integrated IT into their products and have not established a partnership with sharia fintech.